Cadmium-induced apoptosis of Siberian tiger fibroblasts via disrupted intracellular homeostasis. Issue 1 (December 2016) - Wang, Hui; Liu, Zheng; Zhang, Wenxiu; Yuan, Ziao; Yuan, Hongyi; Liu, Xueting; Yang, Chunwen; Guan, Weijun
Abstract Background Heavy metals can cause great harm to Siberian tigers in the natural environment. Cadmium (Cd2+ ) is an environmental contaminant that affects multiple cellular processes, including cell proliferation, differentiation, and survival. It has been shown to induce apoptosis in a variety of cell types and tissues. Results We investigated the apoptotic effects of Cd2+ on Siberian tiger fibroblasts in vitro. Our research revealed the typical signs of apoptosis after Cd2+ exposure. Apoptosis was dose- (0–4.8 μM) and duration-dependent (12–48 h), and proliferation was strongly inhibited. Cd2+ increased the activity of caspase-3, -8, and -9 and disrupted calcium homeostasis by causing oxidative stress and mitochondrial dysfunction. It also increased K+ efflux and altered the mRNA levels of Bax, Bcl-2, caspase-3, caspase-8, Fas, and p53. Conclusions Our results suggest that Cd2+ triggers the apoptosis of Siberian tiger fibroblasts by disturbing intracellular homeostasis. These results will aid in our understanding of the effects of Cd2+ on Siberian tigers and in developing interventions to treat and prevent cadmium poisoning.